MBCL-49. PROGNOSTIC SIGNIFICANCE OF MOLECULAR SUBGROUPS OF MEDULLOBLASTOMA IN CHILDREN RECEIVING IRRADIATION-SPARING REGIMENS. Issue 2 (22nd June 2018) - Yeo, Kee Kiat; Margol, Ashley; Kennedy, Rebekah; Hung, Long; Robison, Nathan; Dhall, Girish; Asgharzadeh, Shahab
Abstract: BACKGROUND: Radiation therapy, while a mainstay of medulloblastoma treatment, is associated with significant age-dependent neurocognitive morbidity in children. Relatively little is known about the subgroup-specific outcome of infants and young children with medulloblastoma treated with irradiation-sparing regimens. METHODS: Infants and young children <10 years of age with medulloblastoma treated with irradiation-sparing regimens (Head Start, COG-99703, or others) at Children's Hospital Los Angeles since 1980 were identified. Molecular subgroup was determined using a 31-gene TaqMan Low Density Array signature. Survival analyses were conducted based on 4 molecular subgroups (WNT, SHH, Group 3, and Group 4). RESULTS: Seventy-six patients with medulloblastoma were identified, with five excluded from survival analysis secondary to non-cancer related deaths. Of these 71 patients, 30 did not receive irradiation as part of their upfront therapy. These patients were divided into SHH (n=17), Group 3 (n=3) and Group 4 subgroups (n=10), with no WNT subgroup identified. Median age at diagnosis was 2.16 (range:0.24-9.80) years. 5-year progression-free survival rates for SHH, Group 3, and Group 4 for this irradiation-sparing cohort were 76.5%±10.3%, 0% and 0%, respectively; 5-year overall survival rates for SHH, Group 3 and Group 4 were 94.0%±5.7%, 0% and 26.7%±15.0%, respectively. CONCLUSION: There was a marked difference in outcome among infants/young children with SHH medulloblastoma vs Group 3/4 medulloblastoma treated with irradiation-sparing regimens. Most patients <10 years of age with SHH medulloblastoma were treated effectively with irradiation-sparing regimens, with high salvageability among those who progressed. Group 3/4 medulloblastoma patients treated without irradiation had extremely poor outcome.